Amyloid detection and typing yield of skin biopsy in systemic amyloidosis and polyneuropathy - Pinton, Sandra; Vacchi, Elena; Chiaro, Giacomo; Raimondi, Andrea; Tzankov, Alexandar; Gerber, Bernhard; Gobbi, Claudio; Kaelin‐Lang, Alain; Melli, Giorgia (Annals of clinical and translational neurology, 2023)
Objective Disease‐modifying therapies are available for amyloidosis but are ineffective if end‐organ damage is severe. As small fiber neuropathy is an early and common feature of amyloidosis, we assessed detection and typing yield of skin biopsy for amyloid in patients with confirmed systemic amyloidosis and neuropathic symptoms. Methods In this case–control study, patients with transthyretin and light chain amyloidosis (ATTRv, ATTRwt, and AL) were consecutively recruited. They were sex and age‐matched to three control groups (1) non‐neuropathic controls (NNC), (2) monoclonal gammopathy of undetermined significance (MGUS), and (3) other neuropathic disease controls (ONC). Patients underwent a double 3 mm skin biopsy in proximal and distal leg. Amyloid index and burden, protein typing by immuno‐electron microscopy, intraepidermal nerve fiber density, electroneuromyography, and clinical characteristics were analyzed. Results We studied 15 subjects with confirmed systemic amyloidosis, 20 NNC, 18 MGUS, and 20 ONC. Amyloid was detected in 100% of patients with amyloidosis (87% in ankle and 73% in thigh). It was not detected in any of the control groups. A small fiber neuropathy was encountered in 100% of amyloidosis patients, in 80% of MGUS, and in 78% of ONC. Amyloid burden was higher in ATTRv, followed by AL and ATTRwt. The ultrastructural examination allowed the identification of the precursor protein by immunotyping in most of the cases. Interpretation Skin biopsy is a minimally invasive test with optimal sensitivity for amyloid. It allows amyloid typing by electron microscope to identify the precursor protein. The diagnostic work up of systemic amyloidosis should include a skin biopsy.